The Influence of Innovation Culture, Transformational Leadership, Organizational Learning on Innovation and Organizational Performance at the Regional Revenue Agency of East Java Province - Usman, Fuad; Riyadi, Slamet; Ardiana, I Dewa Ketut Raka (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The Regional Revenue Agency of East Java Province has the duty and function to collect regional taxes and levies. One type of tax collected is the motor vehicle tax. Organizational performance results related to disbursement of arrears, service quality, and organizational accountability are still not optimal. An indicator that can be seen is that many taxpayers still have not carried out their obligations in paying taxes. Various innovations have been made, but they are not automatically able to improve organizational performance. This study aims to determine the effect of innovation culture, transformational leadership, and organizational learning on innovation and performance. The population in this study are employees at the Regional Revenue Agency office of East Java Province. They have structural positions (Echelon) of as many as 160 people, all of which are used as samples. The data analysis technique used is Structural Equation Modeling (SEM) using AMOS 23. The study's results prove that innovation culture and organizational learning have a significant effect on innovation, transformational leadership has no significant impact on innovation, innovation culture and transformational leadership has a significant effect on organizational performance, organizational learning does not affect organizational performance, and innovation affects organizational performance.